Pendampingan Layout Ulang Area Produksi dan Identifikasi Kebutuhan Teknologi pada UMKM Roti Pakcik untuk Efisiensi Alur Kerja - Tino Hermanto; Iswandi Iswandi; Darianto Darianto; Bobby Umroh; Haniza Haniza; Aginta Yolanda (CV. IRA PUBLISHING, 2025)
This Community Service activity was carried out at the Roti Pakcik Tanjung Morawa MSME through work process observations, discussions with the owner and workers, and recording the condition of the production facility. The activity focused on two fundamental needs of the MSME: improving the layout of the work area to enhance production efficiency and identifying the need for relevant production technology. The observation results showed a crowded work area, unclear functional zoning, and the movement of materials and products across the same area. These conditions increased waiting times, increased the risk of cross-contamination, and complicated quality control. In addition, the production process still relied on manual practices and limited tools, so there was a need for technology in the form of a flour sifting machine to maintain ingredient consistency, a mixer to maintain dough homogeneity according to production capacity, and a bread cutting machine to speed up the process, improve size uniformity, and reduce work fatigue. The activity resulted in a workflow problem map, an initial zoning design, and a list of technology priorities as a basis for further mentoring. These findings position the program as the initial stage of a realistic and field-based MSME production transformation.